2021
DOI: 10.12681/jhvms.25926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alchemilla vulgaris on growth performance, carcass characteristics and some biochemical parameters of heat stressed broilers

Abstract: This study aimed to investigate the effects of Alchemilla vulgaris (A. vulgaris) on growth performance, carcass characteristics, and biochemical parameters in broilers exposed to high environmental temperature conditions. A total of 45 broilers of 21 days of age (Ross 308) were used and grouped as the control group (C), and the groups with the addition of 1% (G1), or 3% (G2) A. vulgaris to chicken diet, respectively. In this study, the body weights of heat stressed broilers were significantly different on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The present perspective demonstrated elevated levels of hematological parameters, particularly monocytes, reflecting a strong hematological response in association with the AVP dietary supplementation. Similarly, a recent study reported that monocyte levels were notably augmented by increasing the dose of AVP in broiler diets [ 49 ]. Furthermore, the MCV, MCH, and platelet distribution width increased significantly in quails fed 1% AVP compared to the control [ 59 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The present perspective demonstrated elevated levels of hematological parameters, particularly monocytes, reflecting a strong hematological response in association with the AVP dietary supplementation. Similarly, a recent study reported that monocyte levels were notably augmented by increasing the dose of AVP in broiler diets [ 49 ]. Furthermore, the MCV, MCH, and platelet distribution width increased significantly in quails fed 1% AVP compared to the control [ 59 ].…”
Section: Discussionmentioning
confidence: 95%
“…Herein, the results reveal better growth performance and feed utilization in all AVP-supplemented groups, and the best results were recorded at higher doses of supplementation. Accordingly, the dietary supplementation of AVP improved the weight gain and FCR of heat-stressed broilers [ 49 ]. In addition, AVP at a dose of 3% improved quail production and the feed conversion ratio and mitigated the negative effects of high temperature [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on broilers showed that; AV known to have anti-inflammatory, antioxidant, and anti-microbial effects did not affect serum MDA, GSH, TAS, TOS, and OSI values (p> 0.05). Although not statistically significant, MDA levels and suppressed lipid peroxidation in a dose-dependent manner decreased in the serum (Köseman et al, 2020).…”
Section: Resultsmentioning
confidence: 65%
“…It was noteworthy that monocyte levels increased significantly because monocytes are phagocytic cells of the blood and support the immune system of the body by killing pathological microorganisms. This suggests that the addition of AV to the diets may contribute to the immune system and the resistance to diseases (Köseman et al, 2020).…”
Section: Resultsmentioning
confidence: 99%